A multi-cycle adjustable full-biodegradable agricultural film base material and a co-extrusion preparation method thereof

CN122914635APending Publication Date: 2026-10-16TAIZHOU SHUOTAI BIOTECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611230365.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

本发明的目的在于提供一种多周期可调全生物降解农用膜基材及其共挤制备方法,以解决现有全生物降解地膜力学性能不足、水蒸气阻隔性能较差、降解周期难以精准调控以及耐候性欠佳的问题

Benefits of technology

(1)本发明采用外层骨架层、中间层功能层和内层控释层的三层结构,骨架层起力学支撑作用,功能层赋予耐候防护功能,控释层负责降解速率的调控,三层协同作用使农用膜基材在保持较好力学性能的同时具备较低的透湿性和可控的降解周期。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of agricultural film preparation, in particular to a multi-period adjustable full-biodegradable agricultural film substrate and a co-extrusion preparation method thereof; the agricultural film substrate comprises an outer skeleton layer, a middle layer functional layer and an inner layer controlled release layer, the skeleton layer comprises PBAT, PLA and modified nano calcium carbonate, the functional layer comprises PBAT, PLA and functional master batch, and the controlled release layer comprises PBAT, PLA and starch-based derivative; the modified nano calcium carbonate is modified by grafting polymerization of amino titanate coupling agent, azo initiator and methyl methacrylate; the preparation method of the substrate is as follows: the raw materials of each layer are mixed and granulated, and then three-layer co-extrusion blown film molding is performed; the prepared agricultural film substrate has good mechanical properties, low moisture permeability and controllable degradation period.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of agricultural film preparation technology, specifically to a multi-cycle adjustable fully biodegradable agricultural film substrate and its co-extrusion preparation method. Background Technology

[0002] Traditional polyethylene agricultural mulch film is difficult to degrade naturally, leading to the accumulation of residual film in the soil over long-term use, which affects crop root growth and soil structure. In recent years, fully biodegradable mulch film, with biodegradable materials such as polybutylene terephthalate (PBAT) and polylactic acid (PLA) as its main raw materials, has gradually become an important alternative to traditional polyethylene mulch film. This type of mulch film can be degraded into carbon dioxide and water through microbial action in the natural environment, providing a feasible path to solve the problem of residual film pollution. However, the promotion of fully biodegradable mulch film still faces many challenges, including high material costs, insufficient mechanical strength, poor water vapor barrier properties, and difficulty in accurately matching the degradation cycle to the growth needs of different crops. Especially in actual field applications, the degradation behavior of mulch film is affected by various environmental factors such as soil temperature, humidity, and microbial communities, often resulting in premature rupture and failure or delayed degradation, making it difficult to meet the differentiated requirements of agricultural production for the service life of mulch film for different crops and regions.

[0003] Chinese patent CN112262695A discloses a three-layer composite high-barrier, controllable, fully biodegradable mulch film and its preparation method. The mulch film comprises an inner slow-release layer, a middle barrier layer, and an outer lifespan control layer. All three layers contain PBAT and PLA. The middle layer also incorporates thermoplastic polyurethane elastomer to reduce water vapor transmission, while the outer layer uses light stabilizers and antioxidants to regulate the degradation cycle. This technology, through its three-layer functionally differentiated structural design, has achieved certain progress in improving the barrier performance and controllable degradation of mulch films.

[0004] While the aforementioned technical solutions have improved the performance of fully biodegradable mulch films to some extent, existing material systems still have shortcomings. Although PBAT possesses good film-forming properties and flexibility, its tensile strength is relatively low, and its water vapor barrier properties are poor. PLA, while having high strength, lacks toughness. The composite materials resulting from the blending of these two materials still have room for improvement in terms of mechanical and barrier properties. Furthermore, current research on how to effectively enhance the interfacial bonding of PBAT and PLA blends and improve the dispersion of inorganic fillers in the matrix is ​​insufficient, limiting further improvements in the overall performance of the mulch film. Summary of the Invention

[0005] (a) Technical problems to be solved The purpose of this invention is to provide a multi-cycle adjustable fully biodegradable agricultural film substrate and its co-extrusion preparation method, so as to solve the problems of insufficient mechanical properties, poor water vapor barrier properties, difficulty in accurately controlling the degradation cycle, and poor weather resistance of existing fully biodegradable mulch films.

[0006] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: A multi-cycle adjustable fully biodegradable agricultural film substrate includes an outer skeleton layer, a middle functional layer, and an inner controlled-release layer.

[0007] Furthermore, the skeleton layer comprises the following raw materials in parts by weight: 60-90 parts of PBAT, 5-30 parts of PLA, and 5-20 parts of modified nano-calcium carbonate.

[0008] Furthermore, the functional layer comprises the following raw materials in parts by weight: 50-80 parts of PBAT, 10-40 parts of PLA, and 3-15 parts of functional masterbatch.

[0009] Furthermore, the controlled-release layer comprises the following raw materials in parts by weight: 40-70 parts of PBAT, 10-30 parts of PLA, and 5-25 parts of starch-based derivatives.

[0010] Furthermore, the modified nano-calcium carbonate is prepared by modification with an amino titanate coupling agent, anchoring with an azo initiator, and graft polymerization with methyl methacrylate.

[0011] Furthermore, the modified nano-calcium carbonate is prepared by the following steps: A1. Mix nano-calcium carbonate with deionized water to prepare a suspension with a mass fraction of 15%–25%. Heat the suspension to 70–90°C and add 2.5%–3.5% of TCA-K44 amino titanate coupling agent by mass of nano-calcium carbonate. Stir the mixture at a constant temperature and temperature for 50–70 min at a stirring rate of 200–400 r / min. After the reaction is completed, separate the solid and liquid components, wash the mixture 2–3 times with deionized water, dry it at 100–110°C for 4–6 h, and pulverize it through a 200–400 mesh sieve to obtain amino-functionalized modified nano-calcium carbonate. A2. Disperse the amino-functionalized modified nano-calcium carbonate obtained in step A1 in deionized water at a solid-liquid ratio of 1:(10-15) g / mL. Disperse at a stirring rate of 300-500 r / min for 20-40 min. Add 0.5%-2.0% of Tween 80 by mass of nano-calcium carbonate. Adjust the pH to 4.5-6.0 with hydrochloric acid. Add azodicyanovalerate and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride. React at 20-30℃ and a stirring rate of 200-400 r / min for 3-5 h. After the reaction, separate the solid and liquid components, wash with deionized water and anhydrous ethanol alternately 2-3 times, and vacuum dry at 40-50℃ for 4-8 h to obtain azo initiator anchored modified nano-calcium carbonate. A3. Disperse the azo initiator-anchored modified nano-calcium carbonate obtained in step A2 in deionized water at a solid-liquid ratio of 1:(8-12) g / mL. Disperse at a stirring rate of 300-500 r / min for 20-40 min. Add methyl methacrylate monomer at a mass ratio of methyl methacrylate to nano-calcium carbonate of 1:(2-4). Purge with nitrogen for 20-40 min. Heat to 70-80℃ and carry out polymerization reaction at a stirring rate of 200-400 r / min. During polymerization, take samples every 0.5 h and monitor the polymerization conversion rate by weighing. When the conversion rate reaches 40%-60%, stop heating and cool to terminate the reaction. After the reaction, separate the solid and liquid, wash with deionized water and anhydrous ethanol alternately 2-3 times, and vacuum dry at 70-90℃ for 4-8 h to obtain modified nano-calcium carbonate.

[0012] Furthermore, in step A2, the amount of azodicyanovalerate is 2% to 4% of the mass of nano-calcium carbonate, and the molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to azodicyanovalerate is (1.0 to 1.5):1.

[0013] Furthermore, the thickness of the skeleton layer is 30% to 50% of the total thickness of the agricultural film substrate, the thickness of the controlled-release layer is 15% to 35% of the total thickness of the agricultural film substrate, and the remainder is the thickness of the functional layer.

[0014] Furthermore, the starch-based derivative is any one of thermoplastic starch, esterified starch, and etherified starch.

[0015] Furthermore, the functional masterbatch is any one of light stabilizer 770, ultraviolet absorber UV-531, and antioxidant 1010.

[0016] A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate includes the following steps: S1. Dry PLA at 80℃ and -0.09 to -0.10 MPa vacuum for 4 to 6 hours. Add the skeleton layer raw material, functional layer raw material and controlled release layer raw material into a high-speed mixer and mix them at room temperature and a stirring rate of 200 to 600 r / min for 10 to 20 minutes to obtain the skeleton layer blend, functional layer blend and controlled release layer blend respectively. S2. The skeleton layer blend, functional layer blend and controlled-release layer blend are respectively added to a twin-screw extruder, melt-extruded and granulated at the melt plasticizing temperature, the screw speed is controlled, the extrudate is cooled in a water bath at a temperature of 20-40℃, and then granulated by a pelletizer to obtain skeleton layer masterbatch, functional layer masterbatch and controlled-release layer masterbatch. S3. The skeleton layer masterbatch, functional layer masterbatch and controlled release layer masterbatch are respectively fed into the three extruders of the three-layer co-extrusion blown film unit, co-extruded and blown film is formed at the co-extrusion molding temperature, the blow-up ratio is controlled, and after traction cooling, it is wound up by the winding device to obtain the multi-cycle adjustable fully biodegradable agricultural film substrate.

[0017] Furthermore, in step S2, the melt plasticizing temperature is 140-200℃, and the temperatures of each section of the twin-screw extruder are set as follows: Zone 1 140-155℃, Zone 2 155-170℃, Zone 3 170-185℃, Zone 4 180-195℃, Zone 5 185-200℃, and the die head temperature is 175-195℃.

[0018] Furthermore, in step S2, the screw rotation speed is 150–350 r / min.

[0019] Furthermore, in step S3, the co-extrusion molding temperature is 160–190°C, and the blow-up ratio is 2.5–4.0.

[0020] (iii) Beneficial technical effects Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention adopts a three-layer structure consisting of an outer skeleton layer, a middle functional layer and an inner controlled-release layer. The skeleton layer provides mechanical support, the functional layer provides weather protection, and the controlled-release layer is responsible for regulating the degradation rate. The three layers work together to enable the agricultural film substrate to maintain good mechanical properties while having low moisture permeability and a controllable degradation cycle.

[0021] (2) This invention modifies nano-calcium carbonate in three steps. The first step uses an amino titanate coupling agent, whose alkoxy groups react with the hydroxyl groups on the surface of nano-calcium carbonate to form titanium-oxygen-calcium bonds, introducing amino groups into the surface of calcium carbonate and changing it from hydrophilic to hydrophobic, which is beneficial for its dispersion in poly(butylene terephthalate / adipate) and polylactic acid matrices. The second step, in the presence of a condensing agent, involves the condensation of the carboxyl groups of azodicyanovalerate with the amino groups on the surface of calcium carbonate to form amide bonds, chemically anchoring azodicyanovalerate to the surface of calcium carbonate, making it less prone to detachment during subsequent processing. The third step involves initiating the polymerization of methyl methacrylate (MMA) through the free radicals generated by the thermal decomposition of MMA, grafting MMA onto the surface of calcium carbonate via carbon-carbon bonds. This grafted layer is compatible with both poly(butylene terephthalate / adipate) and polylactic acid matrices. After the above three-step modification, nano-calcium carbonate can be uniformly dispersed in the matrix and form a tight bond with the matrix, thereby improving the mechanical properties and barrier properties of agricultural film substrate.

[0022] (3) In this invention, a starch-based derivative is added to the controlled-release layer. The hydrophilicity of this raw material is higher than that of polybutylene terephthalate / adipate and polylactic acid. It is preferentially eroded by microorganisms in the soil environment. By adjusting its content in the controlled-release layer, the degradation rate can be changed. At the same time, the starch-based derivative is placed in the inner layer to isolate it from the external environment, so as to avoid degradation too fast and achieve controllable adjustment of the degradation cycle.

[0023] (4) In this invention, light stabilizers, ultraviolet absorbers and antioxidants are added to the functional layer. The light stabilizers and ultraviolet absorbers can reduce the damage of ultraviolet light to the molecular chains of the material, and the antioxidants can inhibit the thermo-oxidative aging process. The three work together to delay the performance degradation of agricultural film substrates during outdoor use. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1 A multi-cycle adjustable fully biodegradable agricultural film substrate includes an outer skeleton layer, a middle functional layer, and an inner controlled-release layer; The skeleton layer comprises the following raw materials in parts by weight: 60 parts PBAT, 5 parts PLA, and 5 parts modified nano calcium carbonate. The functional layer comprises the following raw materials in parts by weight: 50 parts PBAT, 10 parts PLA, and 3 parts light stabilizer 770. The controlled-release layer comprises the following raw materials in parts by weight: 40 parts PBAT, 10 parts PLA, and 5 parts thermoplastic starch. The thickness of the skeleton layer is 30% of the total thickness of the agricultural film substrate, the thickness of the controlled-release layer is 15% of the total thickness of the agricultural film substrate, and the remainder is the thickness of the functional layer.

[0026] The modified nano-calcium carbonate is prepared by the following steps: A1. Nano-calcium carbonate was mixed with deionized water to prepare a suspension with a mass fraction of 15%. The temperature was raised to 70°C, and 2.5% of TCA-K44 amino titanate coupling agent was added. The mixture was stirred at a constant temperature for 50 min at a stirring rate of 200 r / min. After the reaction was completed, the solid and liquid were separated, washed three times with deionized water, dried at 100°C for 6 h, and pulverized through a 200-mesh sieve to obtain amino-functionalized modified nano-calcium carbonate. A2. The amino-functionalized modified nano-calcium carbonate obtained in step A1 was dispersed in deionized water at a solid-liquid ratio of 1:10 g / mL. The dispersion was carried out at a stirring rate of 300 r / min for 20 min. Tween 80, accounting for 0.5% of the mass of nano-calcium carbonate, was added. The pH was adjusted to 4.5 with hydrochloric acid. Azodicyanovalerate and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added. The reaction was carried out at 20 °C and a stirring rate of 200 r / min for 5 h. The amount of azodicyanovalerate was 2% of the mass of nano-calcium carbonate. The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to azodicyanovalerate was 1.0:1. After the reaction was completed, the nano-calcium carbonate was separated into solid and liquid components, washed three times alternately with deionized water and anhydrous ethanol, and dried under vacuum at 40 °C for 8 h to obtain azo initiator anchored modified nano-calcium carbonate. A3. The azo initiator-anchored modified nano-calcium carbonate obtained in step A2 was dispersed in deionized water at a solid-liquid ratio of 1:8 g / mL. The dispersion was carried out at a stirring rate of 300 r / min for 20 min. Methyl methacrylate monomer was added at a mass ratio of methyl methacrylate to nano-calcium carbonate of 1:4. Nitrogen was purged for 20 min to remove oxygen. The temperature was raised to 70℃ and polymerization was carried out at a stirring rate of 200 r / min. During the polymerization process, samples were taken every 0.5 h and the polymerization conversion rate was monitored by weighing. When the conversion rate reached 50%, heating was stopped and the reaction was terminated by cooling. After the reaction, the solid and liquid were separated, and the nano-calcium carbonate was obtained by washing with deionized water and anhydrous ethanol alternately three times and vacuum drying at 70℃ for 8 h.

[0027] A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate includes the following steps: S1. Dry PLA at 80℃ and -0.095MPa vacuum for 4h. Add the skeleton layer raw material, functional layer raw material and controlled release layer raw material into a high-speed mixer and stir and mix at room temperature and 200r / min stirring rate for 10min to obtain the skeleton layer blend, functional layer blend and controlled release layer blend respectively. S2. The skeleton layer blend, functional layer blend, and controlled-release layer blend are respectively added to a twin-screw extruder and melt-extruded into granules at the melt plasticizing temperature. The screw speed is controlled, wherein the melt plasticizing temperature is 175°C, the temperature of each section of the twin-screw extruder is set as follows: zone 1 140°C, zone 2 155°C, zone 3 170°C, zone 4 180°C, zone 5 185°C, the die head temperature is 175°C, the screw speed is 150 r / min, the extrudate is cooled in a water bath at a temperature of 20°C, and then pelletized by a pelletizer to obtain skeleton layer masterbatch, functional layer masterbatch, and controlled-release layer masterbatch. S3. The skeleton layer masterbatch, functional layer masterbatch and controlled-release layer masterbatch are respectively fed into the three extruders of the three-layer co-extrusion blown film unit, and co-extruded and blown film is formed at the co-extrusion molding temperature, and the blow-up ratio is controlled. The co-extrusion molding temperature is 160°C and the blow-up ratio is 2.5. After traction cooling, it is wound up by the winding device to obtain the multi-cycle adjustable fully biodegradable agricultural film substrate.

[0028] Example 2 A multi-cycle adjustable fully biodegradable agricultural film substrate includes an outer skeleton layer, a middle functional layer, and an inner controlled-release layer; The skeleton layer comprises the following raw materials in parts by weight: 68 parts PBAT, 11 parts PLA, and 9 parts modified nano calcium carbonate. The functional layer comprises the following raw materials in parts by weight: 58 parts PBAT, 18 parts PLA, and 6 parts UV absorber UV-531. The controlled-release layer comprises the following raw materials in parts by weight: 48 parts PBAT, 15 parts PLA, and 10 parts esterified starch. The thickness of the skeleton layer is 35% of the total thickness of the agricultural film substrate, the thickness of the controlled-release layer is 20% of the total thickness of the agricultural film substrate, and the remainder is the thickness of the functional layer.

[0029] The modified nano-calcium carbonate is prepared by the following steps: A1. Nano-calcium carbonate was mixed with deionized water to prepare a suspension with a mass fraction of 18%. The temperature was raised to 78℃, and 2.8% of TCA-K44 amino titanate coupling agent (by mass of nano-calcium carbonate) was added. The mixture was stirred at a constant temperature and stirred at 250 r / min for 55 min. After the reaction was completed, the solid and liquid were separated, washed three times with deionized water, dried at 103℃ for 5.5 h, and pulverized through a 250 mesh sieve to obtain amino-functionalized modified nano-calcium carbonate. A2. The amino-functionalized modified nano-calcium carbonate obtained in step A1 was dispersed in deionized water at a solid-liquid ratio of 1:12 g / mL. The dispersion was carried out at a stirring rate of 350 r / min for 25 min. Tween 80, accounting for 0.9% of the mass of nano-calcium carbonate, was added. The pH was adjusted to 4.8 with hydrochloric acid. Azodicyanovalerate and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added. The reaction was carried out at 23 °C and a stirring rate of 250 r / min for 4.5 h. The amount of azodicyanovalerate was 2.5% of the mass of nano-calcium carbonate. The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to azodicyanovalerate was 1.13:1. After the reaction was completed, the nano-calcium carbonate was separated into solid and liquid components, washed three times alternately with deionized water and anhydrous ethanol, and dried under vacuum at 43 °C for 7 h to obtain azo initiator-anchored modified nano-calcium carbonate. A3. The azo initiator-anchored modified nano-calcium carbonate obtained in step A2 was dispersed in deionized water at a solid-liquid ratio of 1:9 g / mL. The dispersion was carried out at a stirring rate of 350 r / min for 25 min. Methyl methacrylate monomer was added at a mass ratio of methyl methacrylate to nano-calcium carbonate of 1:3.5. Nitrogen was purged for 25 min to remove oxygen. The temperature was raised to 73℃ and polymerization was carried out at a stirring rate of 250 r / min. During the polymerization process, samples were taken every 0.5 h and the polymerization conversion rate was monitored by weighing. When the conversion rate reached 50%, heating was stopped and the reaction was terminated by cooling. After the reaction, the solid and liquid were separated, and the nano-calcium carbonate was obtained by washing with deionized water and anhydrous ethanol alternately three times and vacuum drying at 75℃ for 7 h.

[0030] A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate includes the following steps: S1. Dry PLA at 80℃ and -0.095MPa vacuum for 4.5h. Add the skeleton layer raw material, functional layer raw material and controlled release layer raw material into a high-speed mixer and mix them at room temperature and 300r / min stirring rate for 13min to obtain the skeleton layer blend, functional layer blend and controlled release layer blend respectively. S2. The skeleton layer blend, functional layer blend, and controlled-release layer blend are respectively added to a twin-screw extruder and melt-extruded into granules at the melt plasticizing temperature. The screw speed is controlled, wherein the melt plasticizing temperature is 180℃, the temperature of each section of the twin-screw extruder is set as follows: zone 1 144℃, zone 2 159℃, zone 3 174℃, zone 4 184℃, zone 5 189℃, the die head temperature is 180℃, the screw speed is 200r / min, the extrudate is cooled in a water bath at a temperature of 25℃, and then pelletized by a pelletizer to obtain skeleton layer masterbatch, functional layer masterbatch, and controlled-release layer masterbatch. S3. The skeleton layer masterbatch, functional layer masterbatch and controlled-release layer masterbatch are respectively fed into the three extruders of the three-layer co-extrusion blown film unit, and co-extruded and blown film is formed at the co-extrusion molding temperature, and the blow-up ratio is controlled. The co-extrusion molding temperature is 168°C and the blow-up ratio is 2.9. After traction cooling, it is wound up by the winding device to obtain the multi-cycle adjustable fully biodegradable agricultural film substrate.

[0031] Example 3 A multi-cycle adjustable fully biodegradable agricultural film substrate includes an outer skeleton layer, a middle functional layer, and an inner controlled-release layer; the skeleton layer includes the following raw materials in parts by weight: 75 parts PBAT, 18 parts PLA, and 13 parts modified nano-calcium carbonate. The functional layer comprises the following raw materials in parts by weight: 65 parts PBAT, 25 parts PLA, and 9 parts antioxidant 1010. The controlled-release layer comprises the following raw materials in parts by weight: 55 parts PBAT, 20 parts PLA, and 15 parts etherified starch. The thickness of the skeleton layer is 40% of the total thickness of the agricultural film substrate, the thickness of the controlled-release layer is 25% of the total thickness of the agricultural film substrate, and the remainder is the thickness of the functional layer.

[0032] The modified nano-calcium carbonate is prepared by the following steps: A1. Nano-calcium carbonate was mixed with deionized water to prepare a suspension with a mass fraction of 20%. The temperature was raised to 80℃, and TCA-K44 amino titanate coupling agent with a mass of 3.0% of nano-calcium carbonate was added. The mixture was stirred at a constant temperature for 60 min at a stirring rate of 300 r / min. After the reaction was completed, the solid and liquid were separated, washed three times with deionized water, dried at 105℃ for 5 h, and pulverized through a 300-mesh sieve to obtain amino-functionalized modified nano-calcium carbonate. A2. The amino-functionalized modified nano-calcium carbonate obtained in step A1 was dispersed in deionized water at a solid-liquid ratio of 1:13 g / mL. The dispersion was carried out at a stirring rate of 400 r / min for 30 min. Tween 80, accounting for 1.3% of the mass of nano-calcium carbonate, was added. The pH was adjusted to 5.3 with hydrochloric acid. Azodicyanovalerate and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added. The reaction was carried out at 25 °C and a stirring rate of 300 r / min for 4 h. The amount of azodicyanovalerate was 3% of the mass of nano-calcium carbonate. The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to azodicyanovalerate was 1.25:1. After the reaction was completed, the nano-calcium carbonate was separated into solid and liquid components, washed three times alternately with deionized water and anhydrous ethanol, and dried under vacuum at 45 °C for 6 h to obtain azo initiator anchored modified nano-calcium carbonate. A3. The azo initiator-anchored modified nano-calcium carbonate obtained in step A2 was dispersed in deionized water at a solid-liquid ratio of 1:10 g / mL. The dispersion was carried out at a stirring rate of 400 r / min for 30 min. Methyl methacrylate monomer was added at a mass ratio of methyl methacrylate to nano-calcium carbonate of 1:3. Nitrogen was purged for 30 min to remove oxygen. The temperature was raised to 75℃ and polymerization was carried out at a stirring rate of 300 r / min. During the polymerization process, samples were taken every 0.5 h and the polymerization conversion rate was monitored by weighing. When the conversion rate reached 50%, heating was stopped and the reaction was terminated by cooling. After the reaction, the solid and liquid were separated, and the nano-calcium carbonate was obtained by washing with deionized water and anhydrous ethanol alternately three times and vacuum drying at 80℃ for 6 h.

[0033] A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate includes the following steps: S1. Dry PLA at 80℃ and -0.095MPa vacuum for 5h. Add the skeleton layer raw material, functional layer raw material and controlled release layer raw material into a high-speed mixer and stir and mix at room temperature and 400r / min stirring rate for 15min to obtain the skeleton layer blend, functional layer blend and controlled release layer blend respectively. S2. The skeleton layer blend, functional layer blend, and controlled-release layer blend are respectively added to a twin-screw extruder and melt-extruded into granules at the melt plasticizing temperature. The screw speed is controlled, wherein the melt plasticizing temperature is 185℃, the temperature of each section of the twin-screw extruder is set as follows: zone 1 148℃, zone 2 163℃, zone 3 178℃, zone 4 188℃, zone 5 193℃, the die head temperature is 185℃, the screw speed is 250r / min, the extrudate is cooled in a water bath at a temperature of 30℃, and then pelletized by a pelletizer to obtain skeleton layer masterbatch, functional layer masterbatch, and controlled-release layer masterbatch. S3. The skeleton layer masterbatch, functional layer masterbatch and controlled-release layer masterbatch are respectively fed into the three extruders of the three-layer co-extrusion blown film unit, and co-extruded and blown film is formed at the co-extrusion molding temperature, and the blow-up ratio is controlled. The co-extrusion molding temperature is 175°C and the blow-up ratio is 3.3. After traction cooling, it is wound up by the winding device to obtain the multi-cycle adjustable fully biodegradable agricultural film substrate.

[0034] Example 4 A multi-cycle adjustable fully biodegradable agricultural film substrate includes an outer skeleton layer, a middle functional layer, and an inner controlled-release layer; The skeleton layer comprises the following raw materials in parts by weight: 83 parts PBAT, 24 parts PLA, and 16 parts modified nano calcium carbonate. The functional layer comprises the following raw materials in parts by weight: 73 parts PBAT, 33 parts PLA, and 12 parts light stabilizer 770; The controlled-release layer comprises the following raw materials in parts by weight: 63 parts PBAT, 25 parts PLA, and 20 parts thermoplastic starch; The thickness of the skeleton layer is 45% of the total thickness of the agricultural film substrate, the thickness of the controlled-release layer is 30% of the total thickness of the agricultural film substrate, and the remainder is the thickness of the functional layer.

[0035] The modified nano-calcium carbonate is prepared by the following steps: A1. Nano-calcium carbonate was mixed with deionized water to prepare a suspension with a mass fraction of 23%. The temperature was raised to 85°C, and TCA-K44 amino titanate coupling agent with a mass of 3.3% of nano-calcium carbonate was added. The mixture was stirred at a constant temperature and stirred at a stirring rate of 350 r / min for 65 min. After the reaction was completed, the solid and liquid were separated, washed three times with deionized water, dried at 108°C for 4.5 h, and pulverized through a 350 mesh sieve to obtain amino-functionalized modified nano-calcium carbonate. A2. The amino-functionalized modified nano-calcium carbonate obtained in step A1 was dispersed in deionized water at a solid-liquid ratio of 1:14 g / mL. The dispersion was carried out at a stirring rate of 450 r / min for 35 min. Tween 80, accounting for 1.6% of the mass of nano-calcium carbonate, was added. The pH was adjusted to 5.8 with hydrochloric acid. Azodicyanovalerate and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added. The reaction was carried out at 28 °C and a stirring rate of 350 r / min for 3.5 h. The amount of azodicyanovalerate was 3.5% of the mass of nano-calcium carbonate. The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to azodicyanovalerate was 1.38:1. After the reaction was completed, the nano-calcium carbonate was separated into solid and liquid components, washed three times alternately with deionized water and anhydrous ethanol, and dried under vacuum at 48 °C for 5 h to obtain azo initiator-anchored modified nano-calcium carbonate. A3. The azo initiator-anchored modified nano-calcium carbonate obtained in step A2 was dispersed in deionized water at a solid-liquid ratio of 1:11 g / mL. The dispersion was carried out at a stirring rate of 450 r / min for 35 min. Methyl methacrylate monomer was added at a mass ratio of methyl methacrylate to nano-calcium carbonate of 1:2.5. Nitrogen was purged for 35 min to remove oxygen. The temperature was raised to 78℃ and polymerization was carried out at a stirring rate of 350 r / min. During the polymerization process, samples were taken every 0.5 h and the polymerization conversion rate was monitored by weighing. When the conversion rate reached 50%, heating was stopped and the reaction was terminated by cooling. After the reaction, the solid and liquid were separated, and the nano-calcium carbonate was obtained by washing with deionized water and anhydrous ethanol alternately three times and vacuum drying at 85℃ for 5 h.

[0036] A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate includes the following steps: S1. Dry PLA at 80℃ and -0.095MPa vacuum for 5.5h. Add the skeleton layer raw material, functional layer raw material and controlled release layer raw material into a high-speed mixer and mix them at room temperature and 500r / min stirring rate for 18min to obtain the skeleton layer blend, functional layer blend and controlled release layer blend respectively. S2. The skeleton layer blend, functional layer blend, and controlled-release layer blend are respectively added to a twin-screw extruder and melt-extruded into granules at the melt plasticizing temperature. The screw speed is controlled. The melt plasticizing temperature is 190°C. The temperatures of each section of the twin-screw extruder are set as follows: Zone 1 151°C, Zone 2 166°C, Zone 3 181°C, Zone 4 191°C, Zone 5 196°C, and the die head temperature is 190°C. The screw speed is 300 r / min. The extrudate is cooled in a water bath at a temperature of 35°C and then pelletized by a pelletizer to obtain skeleton layer masterbatch, functional layer masterbatch, and controlled-release layer masterbatch. S3. The skeleton layer masterbatch, functional layer masterbatch and controlled-release layer masterbatch are respectively fed into the three extruders of the three-layer co-extrusion blown film unit, and co-extruded and blown film is formed at the co-extrusion molding temperature, and the blow-up ratio is controlled. The co-extrusion molding temperature is 183°C and the blow-up ratio is 3.6. After traction cooling, it is wound up by the winding device to obtain the multi-cycle adjustable fully biodegradable agricultural film substrate.

[0037] Example 5 A multi-cycle adjustable fully biodegradable agricultural film substrate includes an outer skeleton layer, a middle functional layer, and an inner controlled-release layer; The skeleton layer comprises the following raw materials in parts by weight: 90 parts PBAT, 30 parts PLA, and 20 parts modified nano calcium carbonate. The functional layer comprises the following raw materials in parts by weight: 80 parts PBAT, 40 parts PLA, and 15 parts UV absorber UV-531. The controlled-release layer comprises the following raw materials in parts by weight: 70 parts PBAT, 30 parts PLA, and 25 parts esterified starch. The thickness of the skeleton layer is 50% of the total thickness of the agricultural film substrate, the thickness of the controlled-release layer is 35% of the total thickness of the agricultural film substrate, and the remainder is the thickness of the functional layer.

[0038] The modified nano-calcium carbonate is prepared by the following steps: A1. Nano-calcium carbonate was mixed with deionized water to prepare a suspension with a mass fraction of 25%. The temperature was raised to 90°C, and TCA-K44 amino titanate coupling agent accounting for 3.5% of the mass of nano-calcium carbonate was added. The mixture was stirred at a constant temperature and stirred at a stirring rate of 400 r / min for 70 min. After the reaction was completed, the solid and liquid were separated, washed three times with deionized water, dried at 110°C for 4 h, and pulverized through a 400-mesh sieve to obtain amino-functionalized modified nano-calcium carbonate. A2. The amino-functionalized modified nano-calcium carbonate obtained in step A1 was dispersed in deionized water at a solid-liquid ratio of 1:15 g / mL. The dispersion was carried out at a stirring rate of 500 r / min for 40 min. Tween 80, accounting for 2.0% of the mass of nano-calcium carbonate, was added. The pH was adjusted to 6.0 with hydrochloric acid. Azodicyanovalerate and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added. The reaction was carried out at 30 °C and a stirring rate of 400 r / min for 3 h. The amount of azodicyanovalerate was 4% of the mass of nano-calcium carbonate. The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to azodicyanovalerate was 1.5:1. After the reaction was completed, the nano-calcium carbonate was separated into solid and liquid components, washed three times alternately with deionized water and anhydrous ethanol, and dried under vacuum at 50 °C for 4 h to obtain azo initiator anchored modified nano-calcium carbonate. A3. The azo initiator-anchored modified nano-calcium carbonate obtained in step A2 was dispersed in deionized water at a solid-liquid ratio of 1:12 g / mL. The dispersion was carried out at a stirring rate of 500 r / min for 40 min. Methyl methacrylate monomer was added at a mass ratio of methyl methacrylate to nano-calcium carbonate of 1:2. Nitrogen was purged for oxygen removal for 40 min. The temperature was raised to 80℃ and polymerization was carried out at a stirring rate of 400 r / min. During the polymerization process, samples were taken every 0.5 h and the polymerization conversion rate was monitored by weighing. When the conversion rate reached 50%, heating was stopped and the reaction was terminated by cooling. After the reaction, the solid and liquid were separated, and the nano-calcium carbonate was obtained by washing with deionized water and anhydrous ethanol alternately three times and vacuum drying at 90℃ for 4 h.

[0039] A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate includes the following steps: S1. Dry PLA at 80℃ and -0.095MPa vacuum for 6h. Add the skeleton layer raw material, functional layer raw material and controlled release layer raw material into a high-speed mixer and mix them at room temperature and 600r / min stirring rate for 20min to obtain the skeleton layer blend, functional layer blend and controlled release layer blend respectively. S2. The skeleton layer blend, functional layer blend, and controlled-release layer blend are respectively added to a twin-screw extruder and melt-extruded into granules at the melt plasticizing temperature. The screw speed is controlled, wherein the melt plasticizing temperature is 195℃, the temperature of each section of the twin-screw extruder is set as follows: zone 1 155℃, zone 2 170℃, zone 3 185℃, zone 4 195℃, zone 5 200℃, the die head temperature is 195℃, the screw speed is 350r / min, the extrudate is cooled in a water bath at a temperature of 40℃, and then pelletized by a pelletizer to obtain skeleton layer masterbatch, functional layer masterbatch, and controlled-release layer masterbatch. S3. The skeleton layer masterbatch, functional layer masterbatch and controlled-release layer masterbatch are respectively fed into the three extruders of the three-layer co-extrusion blown film unit, and co-extruded and blown film is formed at the co-extrusion molding temperature, and the blow-up ratio is controlled. The co-extrusion molding temperature is 190°C and the blow-up ratio is 4.0. After traction cooling, it is wound up by the winding device to obtain the multi-cycle adjustable fully biodegradable agricultural film substrate.

[0040] Comparative Example 1 A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate, compared with the co-extrusion preparation method for the agricultural film substrate in Example 1, the main difference is that: in this comparative example, the skeleton layer uses an equal amount of unmodified nano-calcium carbonate instead of modified nano-calcium carbonate, that is, the modification treatment in steps A1 to A3 is not performed, and the other components and preparation methods are completely consistent with those in Example 1.

[0041] Comparative Example 2 A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate, compared with the co-extrusion preparation method for the agricultural film substrate in Example 1, has the following main difference: 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is not added in step A2 of this comparative example, and azodicyanovalerate and amino-functionalized nano-calcium carbonate are directly stirred and reacted at 20°C for 5 hours. Other components and preparation methods are completely consistent with those in Example 1.

[0042] Comparative Example 3 A co-extrusion preparation method for a multi-cycle adjustable fully biodegradable agricultural film substrate, compared with the co-extrusion preparation method for the agricultural film substrate in Example 1, has the following main difference: the azo initiator-anchored modified nano-calcium carbonate obtained in step A2 of this comparative example is used directly as a filler in the skeleton layer without being treated in step A3, and the other components and preparation methods are completely consistent with those in Example 1.

[0043] Performance testing: The agricultural film substrates prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to the following relevant performance tests, and the test results are shown in Table 1: (1) Tensile strength and elongation at break: Referring to GB / T 1040.3, the agricultural film substrate is cut into dumbbell-shaped specimens along the longitudinal and transverse directions respectively. The specimens are conditioned in a standard environment with a temperature of 23℃ and a relative humidity of 50% for no less than 16h. After conditioning, the specimens are tested at a tensile speed of 50mm / min under the same environmental conditions. The tensile strength is calculated according to the method specified in GB / T 1040.1. The arithmetic mean of 5 specimens in the longitudinal and transverse directions is taken as the test result. (2) Water vapor transmission rate: Referring to GB / T 1037, the sample was sealed in the mouth of a permeation cup containing desiccant (anhydrous calcium chloride, dried in an oven at 200℃ for at least 2 hours before use). The permeation cup was placed in a constant temperature and humidity chamber at 38℃ and 90% relative humidity. The mass of the permeation cup was weighed every 24 hours until the change rate of the mass increment between the two tests did not exceed 5%. The water vapor transmission rate was calculated according to the method specified in the standard, and the arithmetic mean of the three samples was taken as the test result. (3) Degradation cycle: Referring to GB / T 19277.1, the agricultural film substrate is cut into samples of appropriate size, mixed with the inoculum that has been pre-composted, and placed in a composting reaction container. The composting temperature is controlled at 58℃, the moisture content is 55%, the pH is 7, the carbon-nitrogen ratio (C / N) is 27:1, and the oxygen concentration is not less than 6%. The carbon dioxide release of the samples is measured periodically, and the biodegradation rate is calculated based on the carbon dioxide release. The time required for the biodegradation rate to reach more than 90% is taken as the degradation cycle, and the arithmetic mean of 3 samples is taken as the test result. (4) Tensile strength retention rate: Referring to GB / T 16422.2, the agricultural film substrate sample was placed in a xenon arc lamp aging test chamber, using a sunlight filter, with the irradiance set to 0.55W / (m²·nm)@340nm, the black standard temperature set to 65℃, and the relative humidity set to 50%. After exposure for 240h according to the standard cycle mode, the sample was taken out. After the aged sample was conditioned in the standard environment for no less than 16h, the tensile strength was tested according to GB / T 1040.1. The tensile strength retention rate after ultraviolet aging was calculated according to the method specified in GB / T 16422.2, and the arithmetic mean of 5 samples was taken as the test result.

[0044] Table 1 Example 1 31.8 305 2.46 4.3 85.2 Example 2 34.1 344 2.28 4.1 88.7 Example 3 37.6 368 1.98 3.8 92.3 Example 4 36.2 351 2.07 3.4 94.1 Example 5 35.1 339 2.18 3.1 91.6 Comparative Example 1 26.3 258 2.83 3.0 74.6 Comparative Example 2 28.7 284 2.61 3.6 78.3 Comparative Example 3 25.1 237 3.05 2.5 68.9 As can be seen from the test results in Table 1, the agricultural film substrates prepared in Examples 1-5 of this invention are superior to the comparative examples in terms of mechanical properties, barrier properties, and weather resistance. Comparative Example 1 uses unmodified nano-calcium carbonate. The high surface polarity of calcium carbonate results in high interfacial tension with the PBAT / PLA matrix, leading to filler agglomeration and stress concentration points, resulting in poor tensile and barrier properties. Comparative Example 2 lacks 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride. The carboxyl group of azodicyanopentanoic acid cannot be activated by 1-ethyl-(3-dimethylaminopropyl)carbodiimide to form an O-acylisourea intermediate. The condensation reaction efficiency with the amino group at room temperature is low, resulting in insufficient amide bond anchoring, a decreased polymethyl methacrylate grafting rate, and limited interfacial bonding between nano-calcium carbonate and the matrix. Although its performance is superior to Comparative Example 1, it is still inferior to the examples. Although Comparative Example 3 successfully anchored azodicyanovalerate but did not undergo methyl methacrylate graft polymerization, the surface-anchored azodicyanovalerate underwent thermal decomposition at high temperatures during subsequent melt processing, generating free radicals that caused the molecular chains of the matrix to break, resulting in significant deterioration of mechanical properties. At the same time, the nitrogen gas generated by the decomposition of azodicyanovalerate would escape and form microporous defects, further reducing the water vapor barrier properties and the controllability of degradation.

[0045] This demonstrates that the present invention introduces amino groups onto the surface of nano-calcium carbonate using an amino titanate coupling agent, anchors these groups via azodicyanovalerate amide bonds mediated by 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and then forms a polymethyl methacrylate (PMMA) coating layer through PMMA graft polymerization. The connection between the calcium carbonate surface and the PMMA coating layer is chemically bonded, and the PMMA coating layer is tightly bonded to the PBAT / PLA matrix through compatibility. This three-step synergistic process achieves uniform dispersion and interfacial strengthening of nano-calcium carbonate in the matrix, effectively improving the overall performance of the agricultural film substrate.

[0046] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0047] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A multi-period adjustable fully biodegradable agricultural film substrate, characterized in that, It includes an outer framework layer, an intermediate functional layer, and an inner controlled-release layer; The skeleton layer comprises the following raw materials in parts by weight: 60-90 parts of PBAT, 5-30 parts of PLA, and 5-20 parts of modified nano-calcium carbonate. The functional layer comprises the following raw materials in parts by weight: 50-80 parts of PBAT, 10-40 parts of PLA, and 3-15 parts of functional masterbatch. The controlled-release layer comprises the following raw materials in parts by weight: 40-70 parts of PBAT, 10-30 parts of PLA, and 5-25 parts of starch-based derivatives. The modified nano-calcium carbonate is prepared by modification with an amino titanate coupling agent, anchoring with an azo initiator, and graft polymerization with methyl methacrylate.

2. The modified nano-calcium carbonate of the multi-period adjustable fully biodegradable agricultural film substrate according to claim 1, wherein the preparation method comprises the following steps: A1. Mix nano-calcium carbonate with deionized water to prepare a suspension with a mass fraction of 15% to 25%. Heat the solution to 70 to 90°C and add 2.5% to 3.5% of TCA-K44 amino titanate coupling agent by mass of nano-calcium carbonate. Stir the solution at a constant temperature for 50 to 70 minutes. After the reaction is completed, separate the solid and liquid components, wash, dry, pulverize and sieve to obtain amino-functionalized modified nano-calcium carbonate. A2. Disperse the amino-functionalized modified nano-calcium carbonate obtained in step A1 in deionized water with a solid-liquid ratio of 1:(10-15) g / mL, add 0.5%-2.0% of Tween 80 by mass of nano-calcium carbonate, adjust the pH to 4.5-6.0, add azodicyanovalerate and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir and react at 20-30℃ for 3-5 h, and after the reaction is completed, separate the solid and liquid, wash and dry to obtain azo initiator anchored modified nano-calcium carbonate; A3. Disperse the azo initiator-anchored modified nano-calcium carbonate obtained in step A2 in deionized water with a solid-liquid ratio of 1:(8-12) g / mL. Add methyl methacrylate monomer with a mass ratio of methyl methacrylate to nano-calcium carbonate of 1:(2-4). Purge with nitrogen to remove oxygen and heat to 70-80℃ for polymerization. During polymerization, take samples to monitor the polymerization conversion rate. When the conversion rate reaches 40%-60%, stop heating and cool to terminate the reaction. After the reaction, separate the solid and liquid, wash, and dry to obtain modified nano-calcium carbonate.

3. The multi-period adjustable fully biodegradable agricultural film substrate according to claim 1, characterized in that, In step A2, the amount of azodicyanovalerate is 2% to 4% of the mass of nano-calcium carbonate, and the molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to azodicyanovalerate is (1.0 to 1.5):

1.

4. The multi-period adjustable fully biodegradable agricultural film substrate according to claim 1, characterized in that, The thickness of the skeleton layer is 30% to 50% of the total thickness of the agricultural film substrate, the thickness of the controlled-release layer is 15% to 35% of the total thickness of the agricultural film substrate, and the remainder is the thickness of the functional layer.

5. The multi-period adjustable fully biodegradable agricultural film substrate according to claim 1, characterized in that, The starch-based derivative is any one of thermoplastic starch, esterified starch, or etherified starch.

6. The multi-period adjustable fully biodegradable agricultural film substrate according to claim 1, characterized in that, The functional masterbatch is any one of light stabilizer 770, ultraviolet absorber UV-531, and antioxidant 1010.

7. A method for co-extruding a multi-cycle adjustable fully biodegradable agricultural film substrate, characterized in that, Includes the following steps: S1. Dry PLA under vacuum at 80℃ for 4-6 hours. Add the skeleton layer raw material, functional layer raw material and controlled release layer raw material into a high-speed mixer and stir and mix them evenly at room temperature to obtain the skeleton layer blend, functional layer blend and controlled release layer blend respectively. S2. The skeleton layer blend, functional layer blend and controlled-release layer blend are respectively added to a twin-screw extruder, melt-extruded and granulated at the melt plasticizing temperature, and the screw speed is controlled. After being drawn into strands, cooled and pelletized, skeleton layer masterbatch, functional layer masterbatch and controlled-release layer masterbatch are obtained. S3. The skeleton layer masterbatch, functional layer masterbatch and controlled-release layer masterbatch are respectively fed into the three extruders of the three-layer co-extrusion blown film unit, co-extruded and blown film is formed at the co-extrusion molding temperature, the blow-up ratio is controlled, and after traction cooling, it is wound up to obtain the multi-cycle adjustable fully biodegradable agricultural film substrate.

8. The co-extrusion preparation method of the multi-period adjustable fully biodegradable agricultural film substrate according to claim 7, characterized in that, In step S2, the melt plasticizing temperature is 140-200℃, and the temperature settings of each section of the twin-screw extruder are: zone 1 140-155℃, zone 2 155-170℃, zone 3 170-185℃, zone 4 180-195℃, zone 5 185-200℃, and the die head temperature is 175-195℃.

9. The method for preparing multi-cycle adjustable fully biodegradable agricultural film substrate by co-extrusion according to claim 7, characterized in that, In step S2, the screw rotation speed is 150-350 r / min.

10. The co-extrusion preparation method of the multi-period adjustable fully biodegradable agricultural film substrate according to claim 7, characterized in that, In step S3, the co-extrusion molding temperature is 160-190°C, and the blow-up ratio is 2.5-4.0.

Citation Information

Patent Citations

  • Three-layer composite high-barrier controllable full-biodegradable mulching film and preparation method thereof

    CN112262695A